2023
DOI: 10.46606/eajess2023v04i03.0287
|View full text |Cite
|
Sign up to set email alerts
|

Educators’ Perspectives on Usability of the Moodle LMS: A Case of the National Institute of Transport, Tanzania

Neema Phillip Bhalalusesa,
Fatma Said Kombo,
Peter Godwin Mwakalinga
et al.

Abstract: The purpose of this study was to assess the usability of the Moodle LMS at the National Institute of Transport in Tanzania. The study employed a descriptive research design that involved the use of a questionnaires and interview to collect data from 35 educators who were using the Moodle LMS. Quantitative data was analyzed using the SPSS while qualitative data involved content analysis. The study identified effectiveness, satisfaction, memorability, learnability and errors factors to be used to assess usabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The results showed that memorability in Moodle assessment is high, making Moodle userfriendly, which is also consistent with the study by [62], [68]. Finally, user satisfaction is crucial to usability, measuring how content users are with the LMS [65].…”
Section: A Review Of Usability For Learning Management System (Lms)supporting
confidence: 86%
See 3 more Smart Citations
“…The results showed that memorability in Moodle assessment is high, making Moodle userfriendly, which is also consistent with the study by [62], [68]. Finally, user satisfaction is crucial to usability, measuring how content users are with the LMS [65].…”
Section: A Review Of Usability For Learning Management System (Lms)supporting
confidence: 86%
“…The memorability attributes for Moodle have also been reported by [65], whereby the login icon is easy to remember, making it easier for users to memorise the steps to log into the LMS. The results showed that memorability in Moodle assessment is high, making Moodle userfriendly, which is also consistent with the study by [62], [68].…”
Section: A Review Of Usability For Learning Management System (Lms)mentioning
confidence: 91%
See 2 more Smart Citations
“…According to existing scholarly literature, the impact of e-learning on students' learning outcomes, academic achievements, and satisfaction levels has been widely acknowledged (Abramson et al, 2015;Kuliya & Usman, 2021). Moreover, it has been observed that the intention to use e-learning systems plays a crucial role in the adoption and implementation of online educational programs in various countries (Bhalalusesa et al, 2023;Abramson et al, 2015;Abhirami & Devi, 2022;Kuliya & Usman, 2021;Ramadiani et al, 2017;Revythi & Tselios, 2019). However, previous research has engaged in a discourse concerning the direct and indirect impacts of elearning platforms on academic achievement (Kuliya & Usman, 2021;Chahal & Rani, 2022;Mailizar et al, 2021;Tawafak et al, 2021;Al-Adwan & Al-Debei, 2023).…”
Section: Introductionmentioning
confidence: 99%